Disparitas Dispensasi Kawin dan Perlindungan Anak: Analisis Kritis Terhadap Undang-Undang Nomor 16 Tahun 2019 dan Undang-Undang Nomor 35 Tahun 2014 - Dini Shantya; Riyan Ramdani; Ali Khosim (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Underage marriage or often called child marriage is a marriage carried out by someone who is still under the age specified in the legislation through a marriage dispensation to the religious court. In fact, there are still many cases of child marriage even though there have been changes in the minimum age regulations for marriage through Law Number 16 of 2019. The purpose of this study is to analyze the basis for consideration of Law Number 16 of 2019 in determining marriage dispensation, understand the basis for legal considerations in preventing child marriage, and review the harmony of norms between marriage dispensation and child protection in preventing child marriage. This study uses a library research method with a normative legal approach, which is carried out through an analysis of the text of relevant laws and regulations. The results of the study show that there is disharmony between the regulations on marriage dispensation and the legal provisions governing child protection. This difference in interpretation causes inconsistency in the application of the law, which is a challenge for judges when they have to decide on marriage dispensation cases. In situations like this, the judge is required to make a wise decision by considering urgent reasons and two possible risks, both of which could have a major impact on the child's future.